Clinical and Genetic Mapping of X Chromosome in the X-linked Dominant Inherited Alport′s syndrome - Dai Yong; Huang Yuanshuai; He Xiaolei; Wang Shayan; Huang Ruifang; Tang Min; Hu Chenxiao (Saudi Journal of Kidney Diseases and Transplantation, 2008)
To study the hereditary mode and clinical characteristics and detect mutations of gene COL4A5 encoding type IV collagen a5 chain among family members of an X-linked dominant inherited Alport′s syndrome (AS) family of China, we studied all of 38 family members of whom 2 volunteers underwent renal biopsy. Genomic DNA from all members of the AS family was characterized. All of 51 exons of COL4A5 gene were amplified by polymerase chain reaction (PCR) with the primers synthesized according to the published flanking intervening sequences. PCR products were further analyzed by agarose gel electrophoresis and single strand conformation polymorphism (SSCP) analysis. The study subjects revealing polymorphism by SSCP analysis were directly sequenced. Suspected exons were analyzed with reverse sequencing. Six males and 9 females of the family were diagnosed to have AS by clinical manifestations, family history and/or renal biopsy. Four patients died of end-stage renal disease (ESRD), and 1 patient received kidney transplantation. In the rest of the family members renal function remained normal, however, 22 (58%) revealed hematuria, 11/22 (59%) of them also had proteinuria. The hearing loss was detected in 6 (16%) and ocular lesion in 20 (53%) of family members. By PCR-SSCP analysis, 17 PCR products were identified with different mobility of single strand DNA in volunteers and 9 suspected mutations were revealed with DNA sequencing analysis, but all of which could not be proven by bidirectional sequencing analysis. We conclude that the incidence of hematuria and ophthalmopathy is higher in the X-linked dominant inherited AS in this Chinese family, while some patients have isolated hematuria. Bidirectional sequence analysis should be taken to identify mutations of certain genes. No mutations were found on the region of exons of gene COL4A5.